Enterocolitis Is a Risk Factor for Bowel Perforation in Neonates With Hirschsprung's Disease: A Retrospective Multicenter Study - Tianqi Zhu; Tianqi Zhu; Guofeng Zhang; Xinyao Meng; Xinyao Meng; Jixin Yang; Jixin Yang; Yonghua Niu; Yonghua Niu; Ying He; Ying He; Heying Yang; et al. (Frontiers Media S.A., 2022)
Background and AimWe evaluated the clinical features of neonatal Hirschsprung's disease (HD)-associated bowel perforation (perforated HD) and investigated risk factors related to it.MethodsWe retrospectively collected clinical data of neonates (<1 month of age) with perforated HD from multicenters in China from January 2006 to December 2019. A total of 142 patients (6.7%) with perforated HD were enrolled in the study. A 1:2 matching method was used to compare the clinical information of HD patients with and without bowel perforation during the neonatal period. The risk factors for bowel perforation were identified using univariate and multivariate logistic risk regression analyses.ResultsPerforation site was present in the proximal ganglionic bowel in 101 (71.1%) cases and the distal aganglionosis segment in 41 (28.9%) cases. Adjacent marginal tissue from the perforated intestine revealed varying degrees of inflammatory cell infiltration, and the severity of enterocolitis was higher in the proximal ganglionic bowel than in the distal aganglionosis segment (p < 0.05). In the univariable and multivariable logistic analyses, clinical symptoms, such as vomiting (adjusted OR = 2.06, 95% CI: 2.01-2.88, p < 0.05), and inflammation index in hematologic tests, such as neutrophil proportion (adjusted OR = 1.09, 95% CI: 1.05-1.33, p < 0.05) and CRP (adjusted OR = 2.13, 95% CI: 1.01-3.27, p < 0.05) were associated with increased risk for perforated HD.ConclusionClinical Hirschsprung disease-associated enterocolitis (HAEC) highly correlated with perforated HD. Timely treatment of HAEC should be appropriate therapeutic approaches to prevent perforated HD.